Repetitively pulsed, high-concentration implantation - Ryabchikov A. I. Aleksandr Ilyich (1991, 1991)
We report our work on high dose ion implantation, emphasising the limiting concentration of implanted species that occurs because of surface sputtering. We present experimental results showing that during repetitively pulsed implantation, sputtering of the surface layer can be compensated for by simultaneous neutral atom or low energy ion deposition, thereby arbitrarily high alloying levels can be reached. Experimental data on pulsed implantation of Hf, Tb and Ni into Al, Ti and Fe demonstrate that alloy layers with implanted species concentration of up to 100% can be formed. With implantation of 100 keV Ni into Al and with sputtering compensation and radiation stimulated thermal diffusion conditions, an alloy layer of thickness 0.5 μm and with a Ni concentration of approximately 77 at.% has been obtained. In this paper we review our data on concentration profiles, relating these to the alloy layers and also showing that the layer depth considerably exceeds the ion range. We discuss and generalize our results for high concentration implantation, and consider potential applications of the technique for the modification of surface properties of different materials.